PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA DUMAI - Fazira, Yuni; Mirani, Riska (Graduate Program Magister Manajemen Pendidikan, 2019)
Leadership plays an important role in the organization. The success or failure of an organization is one of them is determined by the resources in the organization. In addition, the factors that play an important role are leadership factors. The main role of leadership is to influence others to achieve the stated goals. In organizations or groups, it is in desperate need of a leader who has the ability to play a role in enhancing the ability of human resources. Therefore leaders in an organization should play a role as much as possible in determining the direction of human resources and as far as possible become change agents, spokespersons and trainers. Role of a leader in the success of an organization is reflected in the leadership style applied to influence his followers. Leadership is guiding, guiding, guiding, building, giving or motivating work, directing the organization, establishing a good communication network, providing efficient supervision, and bringing followers to the target to be addressed in accordance with the time and planning provisions. If the company does not carry out leadership functions, then the company cannot develop.